2004
DOI: 10.1111/j.1750-3639.2004.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

May 2004: Newborn With Intracranial Mass

Abstract: May 2004: We present the case of a male newborn (38th week of gestation) with a 3-week history of a sonographically detected parietal mass of 5-cm diameter. The entire mass was removed at surgery. Surprisingly, microscopy revealed an intracerebral hemorrhage and nests of glycophorin-A immunoreactive blasts and nucleated erythrocytes in the surrounding parenchyma. The final diagnosis was chronic intracerebral hemorrhage of unknown etiology with reactive changes of the surrounding brain tissue and perifocal extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Muller et al concluded that this finding was of no clinical import. There are 4 case reports of extramedullary hematopoiesis in infants-2 in association with large subdural hematomas, 3,4 1 with extensive intracranial papillary endothelial hyperplasia, 5 and the other with semilobar holoprosencephaly, subdural hematoma, and anemia. 6 The potential practical significance of these foci lies elsewhere (ie, in the fact that when a lesion is present in a prominent amount, a pathologist unaware of its occurrence under these circumstances may overinterpret it as a malignant small C hronic subdural hematoma is a common posttraumatic intracranial lesion that has a peak incidence in the sixth and seventh decades of life.…”
mentioning
confidence: 99%
“…Muller et al concluded that this finding was of no clinical import. There are 4 case reports of extramedullary hematopoiesis in infants-2 in association with large subdural hematomas, 3,4 1 with extensive intracranial papillary endothelial hyperplasia, 5 and the other with semilobar holoprosencephaly, subdural hematoma, and anemia. 6 The potential practical significance of these foci lies elsewhere (ie, in the fact that when a lesion is present in a prominent amount, a pathologist unaware of its occurrence under these circumstances may overinterpret it as a malignant small C hronic subdural hematoma is a common posttraumatic intracranial lesion that has a peak incidence in the sixth and seventh decades of life.…”
mentioning
confidence: 99%
“…Olgumuzda hastanın PA akciğer grafisi ve toraks BT'sinde kitlesel lezyonun görülmesi ve kranial MRG'de düzgün sınırlı iki adet kitle görülmesi akciğer kaynaklı metastatik beyin tümörü açısından literatürle uyumludur. Yaptığımız literatür taramasında düzgün sınırlı kitle imajı veren iki adet olguya rastlanmıştır (6,7) . Ancak bu hastalardan biri 5 aylık, diğeri ise yenidoğandır ve her iki hastanın tanısı da geç hemorajik hastalıktır.…”
Section: Discussionunclassified
“…There is one case report in the literature reporting an intracranial parietal mass in a term newborn that was due to chronic intracerebral hemorrhage of unknown etiology with perifocal extramedullary erythropoiesis. 12 Late HD should always be kept in mind in infants who had taken wide spectrum antibiotics, had prolonged gastroenteritis, and had nutritional deficiency, with images of intracranial mass effect.…”
Section: Discussionmentioning
confidence: 99%